Evaluation of Asset Lending System (SIPINSET) (Universitas Negeri Semarang, 2022)
The purpose of this study was to provide an integrated and innovative system that can provide easy access to asset management and lending at the Faculty of Economics, Universitas Negeri Semarang. The need for a digital-based asset lending system is an urgency that must be carried out by the General and Personnel Sub-section in various work units, including the Faculty of Economics, Universitas Negeri Semarang. The system is expected to be able to increase the effectiveness and efficiency in the process of recording, inventorying, and borrowing organizational assets/work units. However, the current problem was that the asset lending system could not be fully integrated automatically, so schedule collisions and data differences between users were often encountered. Therefore, it is necessary to innovate the Asset Lending System (Sipinset) service. This type of research was quantitative with a population of all LK/BSO and education staff in the Faculty of Economics, Unnes. The results of the study recommend the use of feedback from Sipinset users by providing input and suggestions on column features for better development.